Head Teacher Leadership in Nigerian Basic Education: Responsibilities, Challenges, and Prospects - Rasheedat Modupe Oladimeji; Lukman Shehu Akanbi; Risqot Abdullahi; Kamaldeen Olayinka Abdulrauf (Universitas Islam Bunga Bangsa Cirebon, 2024)
Head teachers' administrative capacity and leadership heavily influence the effectiveness of basic education in Nigeria. However, in many public basic schools, particularly in Kwara State, systemic challenges such as overpopulation, inadequate infrastructure, and insufficient funding hinder effective school leadership. This paper investigates head teachers' leadership responsibilities, challenges, and prospects within the Nigerian basic education framework. The paper is motivated by growing concerns over declining educational standards and the increasing complexity of school administration roles in the face of limited institutional support. Adopting a Systematic Literature Review (SLR) methodology, this paper synthesises findings from peer-reviewed journals, policy documents, and empirical studies to identify the core administrative duties of head teachers, assess the barriers they face, and propose strategic interventions. The analysis was guided by thematic synthesis and supported by critical appraisal tools to ensure the inclusion of high-quality literature. The paper reveals that head teachers are responsible for various functions, including instructional leadership, resource management, policy implementation, stakeholder engagement, and quality assurance. However, their effectiveness is undermined by student overpopulation, lack of professional development opportunities, indiscipline among staff and students, poor data systems, and inadequate funding. The paper concludes that empowering head teachers through improved training, inclusive leadership models, infrastructure development, and enhanced supervision mechanisms is crucial for educational reform. The paper contributes knowledge by offering a comprehensive framework for strengthening school leadership and guiding future policy decisions in Nigeria’s basic education sector